500 V SOI lateral pin diode with dual deep‐oxide trenches for fast reverse recovery and suppressed oscillation. Issue 1 (1st January 2016) - Zhu, Jing; Zhang, Long; Sun, Weifeng; Huang, Keqin; Du, Yicheng
Abstract : A 500 V silicon‐on‐insulator (SOI) lateral pin diode is proposed. The proposed structure features dual deep‐oxide trenches (DDOTs) arranged in the i ‐layer. In off‐state, the dual DDOTs can help to sustain the potential between the cathode and the anode. With the breakdown voltage of 500 V level, the i ‐layer length of the proposed structure can be dramatically shortened compared with the conventional SOI diode. The fast reverse recovery is obtained due to the reduced amount of the stored carrier in on‐state. During the reverse recovery, the holes can be trapped by the gap between the adjacent deep‐oxide trenches (DOTs). Therefore, dynamic punch‐through is avoided and suppressed oscillation can be realised. The proposed structure achieves a reverse recovery time of 72 ns which is an improvement by 28% compared with the conventional SOI diode. Meanwhile, the waveform oscillation of the proposed structure is successfully suppressed, which is superior to the normal DOTs SOI lateral pin diode.